2021
DOI: 10.1039/d1sc01389k
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic decarboxylative amidosulfonation enables direct transformation of carboxylic acids to sulfonamides

Abstract: Sulfonamides are now accessible directly from carboxylic acids by a one-step, tricomponent decarboxylative amidosulfonation that provides the missing link between the two key functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Jiang and co-workers used sodium dithionite as the SO 2 source and reductant to generate alkyl sulfinates from activated esters in a sulfone synthesis, although no primary nonbenzylic substrates were included. Larionov has reported the synthesis of alkyl sulfonamides from carboxylic acids, and a recent report has shown that decatungstate photocatalysis can achieve C–H bond sulfination …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang and co-workers used sodium dithionite as the SO 2 source and reductant to generate alkyl sulfinates from activated esters in a sulfone synthesis, although no primary nonbenzylic substrates were included. Larionov has reported the synthesis of alkyl sulfonamides from carboxylic acids, and a recent report has shown that decatungstate photocatalysis can achieve C–H bond sulfination …”
mentioning
confidence: 99%
“…Jiang and co-workers used sodium dithionite as the SO 2 source and reductant to generate alkyl sulfinates from activated esters in a sulfone synthesis, 17 although no primary nonbenzylic substrates were included. Larionov has reported the synthesis of alkyl sulfonamides from carboxylic acids, 18 and a recent report has shown that decatungstate photocatalysis can achieve C−H bond sulfination. 19 2,4,6-Trisubstituted pyridinium (Katritzky) salts, studied by Katritzky and co-workers since the 1970s, 20 have recently seen a surge in interest and have been used as radical precursors, generating alkyl radicals under mild conditions by singleelectron reduction.…”
mentioning
confidence: 99%
“…Nguyen et al also presented the one-step generation of sulfonamides and sulfonyl azides, employing a multicomponent strategy involving aliphatic carboxylic acids, DABSO, and N-centered coupling partners. 305 Exploiting a proton-coupled electron transfer (PCET) mechanism to achieve decarboxylation and the use of a Cu co-catalyst, the authors were able to synthesize a wide range of aliphatic and aromatic sulfonamides and sulfonyl azides with good to excellent yields. Given the importance that the sulfonamide moiety holds as a bioisoster of carboxylic acids especially, this methodology stands out due to its ability to generate this functionality in a one-step reaction under mild conditions.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The importance of this reaction is to design new bioisosteric replacements of medicines bearing carboxylic acids. 39 Through the Pd(II)-catalyzed reaction of aryl iodides and DABSO, aryl ammonium sulfinates were conveniently formed as intermediates. This was transformed to the desired sulfonamides 14 by treating with a wide range of amines as shown in Scheme 10.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%